Utility and reproducibility of 3‐dimensional printed models in pre‐operative planning of complex thoracic tumors. Issue 3 (28th July 2017) - George, Elizabeth; Barile, Maria; Tang, Anji; Wiesel, Ory; Coppolino, Antonio; Giannopoulos, Andreas; Mentzer, Steven; Jaklitsch, Michael; Hunsaker, Andetta; Mitsouras, Dimitrios
Abstract : Background and Objectives: 3D‐printed models are increasingly used for surgical planning. We assessed the utility, accuracy, and reproducibility of 3D printing to assist visualization of complex thoracic tumors for surgical planning. Methods: Models were created from pre‐operative images for three patients using a standard radiology 3D workstation. Operating surgeons assessed model utility using the Gillespie scale (1 = inferior to 4 = superior), and accuracy compared to intraoperative findings. Model variability was assessed for one patient for whom two models were created independently. The models were compared subjectively by surgeons and quantitatively based on overlap of depicted tissues, and differences in tumor volume and proximity to tissues. Results: Models were superior to imaging and 3D visualization for surgical planning (mean score = 3.4), particularly for determining surgical approach (score = 4) and resectability (score = 3.7). Model accuracy was good to excellent. In the two models created for one patient, tissue volumes overlapped by >86.5%, and tumor volume and area of tissues ≤1 mm to the tumor differed by <15% and <1.8 cm 2, respectively. Surgeons considered these differences to have negligible effect on surgical planning. Conclusion: 3D printing assists surgical planning for complex thoracic tumors. Models can be created by radiologists using routine practice tools with sufficient accuracy and clinically negligible variability.